CONCEPT AND RATIONALE OF EVOLUTIONARY BARLEY BREEDING UNDER CLIMATE CHANGE IN JORDAN - Al‐Hajaj, Nawal; Kafawin, Omar (International Journal of Research -GRANTHAALAYAH, 2021)
In this study, we reviewed the climate changing and the impact on crop production, and evolutionary breeding as adaptation key to crop resilience. The increasing climate change impact on the agriculture system has renewed interest to the broadest possible germplasm base for a resilient and sustainable food system. Heterogeneous populations developed through evolutionary plant breeding could be the ideal solution to reduce the effects of environment variability on cereal crop planted under low-input conditions.The study assessed the genetic basis of adaptation of a barley population which evolved in different rainfed locations and years in Jordan without any human selection as suggests model of plant breeding strategy to improve food security, nutrition, income and resilience of smallholder farmers in the dryland regions in the climate change scenarios. The study suggests that the breeder can shift the undesirable traits in evolutionary populations by practicing individual selection for specific adaptations, or individual selection from populations showing wide adaptations and high stability. On the other hand, the breeder can overcome the undesirable traits by keeping the highest variations within the population by seed sieving to remove small seed and plant mowing for tallest head.